U6atac snRNA, the highly divergent counterpart of U6 snRNA, is the specific target that mediates inhibition of AT-AC splicing by the influenza virus NS1 protein. - Wang, W (1998)
The influenza virus NS1 protein inhibits the splicing of the major class of mammalian pre-mRNAs (GU-AG Introns) by binding to a specific stem-bulge in U6 snRNA, thereby blocking the formation of U4/U6 and U2/U6 complexes. The splicing of the minor class of AT-AC introns takes place on spliceosomes that do not contain U6 snRNA, but rather U6atac snRNA-a highly divergent U6 snRNA counterpart. Nonetheless, we demonstrate that the NS1 protein inhibits AT-AC splicing in vitro, and specifically binds to only U6atac snRNA among the five minor class snRNAs. Chemical modification/interference assays show that the NS1 protein binds to the stem-bulge near the 3' end of U6atac snRNA, encompassing nt 82-95 and nt 105-114. Although the sequence of this stem-bulge differs significantly from the sequence of the stem-bulge to which the NS1 protein binds in U6 snRNA, RNA competition experiments Indicate that U6 and U6atac snRNAs likely share the same binding site on the NS1 protein. Previously, the region of U6atac snRNA containing this 3' stem-bulge had not been implicated in any interactions of this snRNA with either U4atac or U12 snRNA. However, as assayed by psoralen crosslinking, we show that the NS1 protein inhibits the formation of U12/U6atac complexes, but not the formation of U4atac/U6atac complexes. We can conclude that the inhibition of AT-AC splicing results largely from the inhibition of formation of U12/U6atac complexes caused by the binding of the NS1 protein to the 3' stem-bulge of U6atac snRNA.